2009
DOI: 10.1007/s11270-009-0218-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in Runoff from Residential Roads in a Coastal Area

Abstract: Non-point sources of nitrogen (N) contribute to pollution of many coastal waters. Road runoff of N has been estimated for busy highways, but residential roads could also be important non-point sources. Here we estimate N in runoff from two small residential roads (average annual daily traffic [AADT] <1,000) and a state highway (AADT=8,800) in a coastal watershed of Massachusetts, USA. The antecedent dry-day traffic was correlated with total dissolved nitrogen (TDN) concentrations at the beginning of each rain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Pollutant concentrations in road runoff varied with land use; the EMCs of TSS, COD, NH 4 , and TP were higher in RA than in AR and IA during rainfall events, especially during the event with a long antecedent dry weather period (Table 3). These findings agree with earlier studies that revealed that RA and IA roads were dominant sources of N and P in road runoff [5,6,15,21,43], and AR were the dominant sources of TSS [21,44,45]. Automobile catalytic converters operate less effectively during the first 1-2 min.…”
Section: Discussionsupporting
confidence: 92%
“…Pollutant concentrations in road runoff varied with land use; the EMCs of TSS, COD, NH 4 , and TP were higher in RA than in AR and IA during rainfall events, especially during the event with a long antecedent dry weather period (Table 3). These findings agree with earlier studies that revealed that RA and IA roads were dominant sources of N and P in road runoff [5,6,15,21,43], and AR were the dominant sources of TSS [21,44,45]. Automobile catalytic converters operate less effectively during the first 1-2 min.…”
Section: Discussionsupporting
confidence: 92%
“…Even without increases in N applications to watersheds, hydrologic alterations that route rainfall efficiently into receiving streams lead to predictable increases in storm-borne delivery of N to surface water ecosystems (e.g., Shields et al 2008;Davidson et al 2010). Collectively, enhanced N loading and highly engineered stormwater routing vastly increase loading of N. For much of the nation, the increased storm severity predicted by many climate change models is likely to further exacerbate this trend.…”
Section: Hydrologic Alteration In Managed Ecosystemsmentioning
confidence: 99%
“…In regions with intensive agriculture (e.g., Denmark), the relative input of N from urban areas is usually negligible (Jeppesen et al, 2007). However, in some countries, such as the United States and Australia, N from urban areas is a key parameter to control the quality of coastal waters (Taylor et al, 2005; Collins et al, 2010; Davidson et al, 2010). The chemical properties of N, as well as the mechanisms for removal of N, differs greatly from that of P. Median concentrations of total N (TN) have been reported as 2.2 mg L −1 for roads and 2.5 mg L −1 for other “high” urban catchments (Duncan, 1999).…”
Section: Nutrients and Organic Mattermentioning
confidence: 99%